Characterization of biodegradable bi-layer films from thermoplastic starch and poly-l-lactic acid - Parlak, Mahmut Ekrem; Uzuner, Kubra; Ozdemir, Sebahat; Kirac Demirel, Fatma Tuba; Dundar, Ayse Neslihan; Sahin, Oya Irmak; Saricaoglu, Furkan Turker (Wiley, 2024)
This study aimed to enhance the oxygen barrier properties of polylactic acid (PLA) film, a biodegradable packaging material with high oxygen permeability (OP). Bi-layer films were produced by coating thermoplastic starch (TPS) onto PLA films in various ratios while maintaining constant film thickness. The mechanical, optical, barrier, thermal, hydrophobicity, moisture sorption, and microstructural properties of the films were analyzed. Increasing the TPS ratio elevated moisture content (MC), water uptake, solubility, and opacity while enhancing UV barrier properties. TPS coating reduced tensile and burst strength but increased the burst deformation of the bi-layer films. Bi-layer film production resulted in a water vapor permeability increase of 59.26%-94.44% compared with neat PLA while decreasing OP by 2.52%-29.66%. The equilibrium moisture content (EMC) rose with higher TPS ratios, displaying type II isotherms. FTIR analysis indicated no chemical interactions between PLA and TPS. Increasing the TPS ratio decreased PLA crystallinity, supporting the mechanical and barrier properties of the bi-layer films. Neat and bi-layer films exhibited smooth, homogeneous surfaces, with a visible interface in the cross-section of the bi-layer films. In conclusion, TPS shows promise as an alternative to improve oxygen barrier properties in PLA films without adversely affecting other properties.
Keywords: biodegradable; biopolymers and renewable polymers; mechanical Properties; polysaccharides; thermoplastics